144k views
5 votes
Prove this (sinx-tanx)(cosx-cotx)=(sinx-1)(cosx-1)

User Marawan
by
6.4k points

2 Answers

0 votes
distribute first
sinx cosx - sinx cotx - cosx tanx+tanx cotx
sinx cosx - sinx (cosx/sinx) - cosx (sinx/cosx) + tanx (cosx/sinx)
sinxcosx - cosx - sinx +1
and factor
cosx(sinx -1) -1(sinx - 1)
(sinx -1)(cosx-1)
User Mikael Jansson
by
6.2k points
1 vote

(sinx−tanx)(cosxcotx)

=(sinxsinxcosx)(cosxcosxsinx)

=sinx(1−1cosx)cosx(1−1sinx)

=sinx(cosxcosx1cosx)cosx(sinxsinx1sinx)

=sinxcosx(cosx−1)cosxsinx(sinx−1)

=(cosx−1)(sinx−1)

User LawrenceGS
by
6.5k points